2012
DOI: 10.1074/jbc.c112.369439
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering of a Short Internal Peptide Activates a tRNA Synthetase Procytokine

Abstract: Background: Many tRNA synthetases have acquired expanded functions unrelated to their canonical aminoacylation function. Results: Structural analysis in solution showed that a subtle conformational change causes pinpointed exposure of an evolutionarily acquired ELR tripeptide of human tyrosyl-tRNA synthetase, which activates its cytokine function. Conclusion:The exposure of ELR of TyrRS confers cytokine activity. Significance: The TyrRS design facilitates functional expansion while retaining its essential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…These activities include major roles in regulating angiogenesis (Xu et al, 2012; Yao et al, 2012), inflammatory responses (Arif et al, 2009; Fu et al, 2012; Lee et al, 2012), mTOR signaling (Bonfils et al, 2012; Han et al, 2012), and tumor growth (Dorrell et al, 2007; Park et al, 2012). In at least some instances, a fragment produced by natural proteolysis is the active factor.…”
Section: Introductionmentioning
confidence: 99%
“…These activities include major roles in regulating angiogenesis (Xu et al, 2012; Yao et al, 2012), inflammatory responses (Arif et al, 2009; Fu et al, 2012; Lee et al, 2012), mTOR signaling (Bonfils et al, 2012; Han et al, 2012), and tumor growth (Dorrell et al, 2007; Park et al, 2012). In at least some instances, a fragment produced by natural proteolysis is the active factor.…”
Section: Introductionmentioning
confidence: 99%
“…2c , left). By breaking the Y341 OH--H-bond to a backbone carbonyl oxygen, a Y341A mutation releases tight tethering of the C-domain to the catalytic domain 15 and its reorientation 16 ( Fig. 2c , right).…”
mentioning
confidence: 99%
“…Analysis of the Y341A mutant of human tyrosyl-tRNA synthetase, a functional mutant that would not crystallize, with HDX MS and SAXS revealed conformational changes essential for activation via uncovering of an internal tripeptide sequence. 50 In the seryl-tRNA synthetase, HDX MS was used 51 to understand why a mutation (F383V) located ∼100 amino acids upstream of the nuclear localization signal (NLS) somehow abolished nuclear localization. The NLS was not resolved in a crystal of the protein, but HDX MS showed that the NLS was protected from exchange in the F383 V mutant versus the wild-type.…”
Section: Protein Structural Characterizationmentioning
confidence: 99%